PROSPECTS AND CURRENT PROBLEMS OF PHYSIOLOGY, BIOCHEMISTRY, AND PATHOPHYSIOLOGY IN MODERN VETERINARY MEDICINE (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
Abstract.Veterinary medicine has undergone significant advancements in recent years, with physiology, biochemistry, and pathophysiology playing crucial roles in diagnosing and managing animal diseases. However, despite these developments, challenges remain in integrating advanced diagnostic tools, addressing emerging diseases, and standardizing therapeutic protocols. This paper explores the prospects and current problems in these fields, emphasizing their implications for modern veterinary medicine